2018
DOI: 10.7717/peerj.5082
|View full text |Cite
|
Sign up to set email alerts
|

Mulch and groundcover effects on soil temperature and moisture, surface reflectance, grapevine water potential, and vineyard weed management

Abstract: The objectives of this research were to identify alternatives to glyphosate for intra-row (under-trellis) vineyard floor management and to evaluate the potential for intra-row and inter-row (alleyway) groundcovers to reduce vegetative vigor of ‘Marquette’ grapevines (Vitis spp.) in a southeast Nebraska vineyard. The experiment was a randomized factorial design with five intra-row treatments (crushed glass mulch [CG], distillers’ grain mulch [DG], creeping red fescue [CRF], non-sprayed control [NSC], and glypho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Straw mulch in present study lowered the daytime soil temperature, and an average decrease of 1.9 and 1.5°C was observed for top and subsoils during the crop period, respectively. This decrease was in line with earlier studies reporting lower soil temperature under straw mulch treatment (Fourie and Freitag, 2010;Gholamhuseini et al, 2019); however, Bavougian et al (2018) reported increased soil temperature under organic mulch suggesting increased microbial activity as a possible reason. Summers et al (2004) found that wheat straw reflected approximately 85% of the visible spectrum of light compared to 41% under bare soil.…”
Section: Soil Moisture and Soil Temperaturesupporting
confidence: 92%
See 1 more Smart Citation
“…Straw mulch in present study lowered the daytime soil temperature, and an average decrease of 1.9 and 1.5°C was observed for top and subsoils during the crop period, respectively. This decrease was in line with earlier studies reporting lower soil temperature under straw mulch treatment (Fourie and Freitag, 2010;Gholamhuseini et al, 2019); however, Bavougian et al (2018) reported increased soil temperature under organic mulch suggesting increased microbial activity as a possible reason. Summers et al (2004) found that wheat straw reflected approximately 85% of the visible spectrum of light compared to 41% under bare soil.…”
Section: Soil Moisture and Soil Temperaturesupporting
confidence: 92%
“…In this study, average soil temperature was lower under mulch treatment compared to no-mulch for summer maize. Radiometric properties of the mulch material and heat conduction between the mulch and the soil surface drive the ability of mulch to moderate soil temperature (Bavougian et al, 2018). Vegetative or organic mulches reduce the heat conduction into and out of the soil, causing cooler soil during the day but warmer soil at night compared to bare soil (Acharya et al, 2018).…”
Section: Soil Moisture and Soil Temperaturementioning
confidence: 99%
“…The treatments showed differences in soil moisture; it was higher for the Bra treatment, probably due to the lower temperature of these soils in the vineyard growth cycle, which prevents evapotranspiration. 74 The green line represents the Bra treatment; after the simulation, the soil moisture sharply increased from 17% to almost 30% in the topsoil (10 cm depth). Similarly, in the Till treatment, represented by orange color, moisture in topsoil increased from 12% to 22%.…”
Section: Resultsmentioning
confidence: 99%
“…California in the USA) listed biodiversity and sustainable soil management practices (Flores, 2017). Cover crops can cover part (between rows) or the entire vineyard floor (between rows and under-trellis) to decrease soil erosion, chemical and nutrient leaching and the need for synthetic weed control (Bavougian and Read, 2018;Karl et al, 2016). In general, certain consumer segments are interested in and show higher WTP for environmentally sustainable wines (Forbes et al, 2009;Sogari et al, 2016;Tait et al, 2019;Ghvanidze et al, 2019;McGarry Wolf and Higgins, 2017).…”
Section: Ijwbr 341mentioning
confidence: 99%